1994
DOI: 10.1111/j.1365-2796.1994.tb00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and transferrin saturation in patients with chronic alcoholic and non‐alcoholic liver diseases

Abstract: Serum ferritin is more frequently elevated in abusing patients with alcoholic liver disease than in patients with other chronic liver diseases such as autoimmune liver diseases and hepatitis C. Because serum ferritin decreases rapidly during abstinence, the measurement of ferritin for the detection of haemochromatosis in patients abusing alcohol should be postponed until the patients are abstaining. Most of the patients with increased serum ferritin have normal transferrin saturation values which can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 20 publications
1
80
1
4
Order By: Relevance
“…Serum ferritin is an extremely sensitive indicator of iron storage status, with hyperferritinemia occurring in the setting of numerous disorders associated with iron overload (hemochromatosis, 60 sickle cell disease, 61 and thalassemia 62 ). Additionally, hyperferritinemia serves as a nonspecific marker for a variety of neoplasms, [63][64][65] infectious diseases, 66-68 alcohol ingestion, 69 and a sedentary lifestyle. 70 While we examined self-reported data regarding a number of chronic diseases as well as recent alcohol ingestion experience, we were unable to explain dif- * Post-traumatic stress disorder was screened for by questionnaire using criteria reported in the Diagnostic and Statistical Manual of Mental Disorder, fourth edition.…”
Section: Resultsmentioning
confidence: 99%
“…Serum ferritin is an extremely sensitive indicator of iron storage status, with hyperferritinemia occurring in the setting of numerous disorders associated with iron overload (hemochromatosis, 60 sickle cell disease, 61 and thalassemia 62 ). Additionally, hyperferritinemia serves as a nonspecific marker for a variety of neoplasms, [63][64][65] infectious diseases, 66-68 alcohol ingestion, 69 and a sedentary lifestyle. 70 While we examined self-reported data regarding a number of chronic diseases as well as recent alcohol ingestion experience, we were unable to explain dif- * Post-traumatic stress disorder was screened for by questionnaire using criteria reported in the Diagnostic and Statistical Manual of Mental Disorder, fourth edition.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, iron overload was more intense in the presence of liver disease, as shown by higher serum concentrations of ferritin and transferrin saturation. Although ferritin and transferrin saturation may be questioned as markers of iron overload in the presence of liver disease, since ferritin elevation may result from necroinflammatory activity, and decreased hepatic protein production may occur secondary to liver disease [36] , resulting in lower TIBC and higher transferrin saturation, previous studies in patients with liver disease have shown significantly higher ferritin levels in patients with alcohol-related liver disease [12] . Furthermore, in the present study, we observed a positive correlation between serum ferritin and the degree of hepatic iron deposition in patients who had a liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Alcoholic liver disease (ALD) is often associated with elevated serum iron indices and hepatic iron overload [11][12][13][14] . Iron is also believed to be central in the pathogenesis of ALD, and some reports show iron overload as a predictive indicator of higher mortality [15] , and development of hepatocellular carcinoma [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Published series of gastrointestinal endoscopy in patients with iron deficiency anemia vary in the criteria they use to diagnose the iron deficiency, but most studies use ferritin below 20-50 ng/mL [1][2][3][4][5]. However, studies using bone marrow hemosiderin as the gold standard have shown that in older patients and/or in patients with comorbidites, iron deficiency anemia is often present despite normal levels of ferritin [6][7][8][9][10]. In a study of 101 anemic veterans who underwent bone marrow examination with hemosiderin stain, the mean ferritin in irondeficient patients was 53 ng/mL, with a range of 9-518 ng/mL [6].…”
Section: Introductionmentioning
confidence: 99%